PENGARUH MEDIA QUIZIZZ TERHADAP HASIL BELAJAR MENULIS LATIHAN TEKS RUPANG SISWA KELAS XI-7 SMA NEGERI 1 MENGANTI - Anisah, Nurul; Wahyuningsih, Fahmi (LATERNE, 2023)
Writing of this thesis is motivated by the problems of students whose learning results, especially in the field of German language subjects, are still considered not to meet KKM standards. This is known from the interview with a German teacher SMA Negeri 1 Menganti. In addition, SMA Negeri 1 Menganti is still accustomed to using conventional learning methods or lecture methods that make the classroom atmosphere during learning quickly bored and sleepy. For solutions that can be offered so that students can be resolved and help increase learning motivation so that students ’ learning hsil increases, Quizizz media will be used as a learning medium. The formulation of the problem is: how media Quizizz affect learning outcomes text writing exercises rumpang in Class XI=7 SMA Negeri 1 Menganti. The place of research is in SMA Negeri 1 Menganti, Gresik. The object of research is all students of Class XI-7 SMA Negeri 1 Menganti totaling 30 students. This research method using quantitative research approach with experimental design pretest-posttest one group. Research Data obtained from pretest and posttest results were analyzed using normality test, n-Gain Test, and Wilcoxon test, with significant results (Sig. 2-tailed) amounted to .000<0.05 which means that the hypothesis is accepted, there is an influence of Quizizz media on the learning outcomes of students in Class XI-7 SMA Negeri 1 Menganti.